2021
DOI: 10.9734/jpri/2021/v33i831207
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Volleyball Training on Athletes' Liver Enzymes and Muscle Damage Markers

Abstract: Aims: It is seen that regular exercises cause physiological changes in the organism. The effects of such a training are not known especially on liver enzymes and muscle damages. In this regard, this study aimed to determine the effects of long-term volleyball training on athletes’ indicators of liver enzymes and muscle damages. Methodology: 20 male volunteer athletes in volleyball branch participated in the study. In the study, a 12-week training program was applied to the athletes four days a week, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In a different study, Erdoğan (2021) determined that the conditioning training he applied in addition to volleyball training caused changes in the liver enzymes and muscle damage markers of the athletes (13).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…In a different study, Erdoğan (2021) determined that the conditioning training he applied in addition to volleyball training caused changes in the liver enzymes and muscle damage markers of the athletes (13).…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…After 12 sessions of weight lifting, serum CK concentrations increased by about 29% [24]. Erdogan [25] demonstrated that 12 weeks of regular volleyball training at a maximal heart rate raised the level of muscle injury biomarkers, such as CK and CK-MB (myocardial izoenzyme) [25]. Most importantly, a recent study reported a higher level of total CK and CK-MB in individuals with depressive disorders [26].…”
Section: Introductionmentioning
confidence: 99%